FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH DAERAH: OPINI AUDIT SEBAGAI VARIABEL MODERASI - Thio Arya Raditya (2022)
This study was conducted to examine the factors that can affect the level of disclosure of local government financial statements, this study uses audit opinion as a moderating variable. The ratio of financial independence, capital expenditure, intergovernmental revenue, and legislative size are independent variables used in this study, the level of disclosure of local government financial statements (LKPD) is the dependent variable. This study uses a population of local government financial statements in Indonesia that have been audited by BPK. The number of research samples used were 338 local/city governments on the island of Java for the period 2018-2020 with purposive sampling. This study performs multiple linear regression analysis using the STATA version 16 application. Based on the test results, it was found that the financial independence ratio had a significant effect on the level of LKPD disclosure. In addition, intergovernmental revenue also has a significant effect on the level of LKPD disclosure. Meanwhile, capital expenditure has no significant effect on the level of LKPD disclosure. Furthermore, legislative size has no significant effect on the level of disclosure of LKPD. Audit opinion as a moderating variable, can moderate the ratio of financial independence and legislative size but does not moderate capital expenditure and intergovernmental revenue on the level of disclosure of LKPD.